2020
DOI: 10.3390/microorganisms8030387
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lactic Acid Bacteria Mixture: Macrophage-Targeted Prophylactic Intervention in Colorectal Cancer Management

Abstract: Colorectal cancer (CRC) is one of the most common forms of cancer. Its onset from chronic inflammation is widely accepted. Moreover, dysbiosis plays an undeniable role, thus the use of probiotics in CRC has been suggested. They exhibit both anti- and pro-inflammatory properties and restore balance in the microbiota. The aim of this study was to investigate the immunomodulatory properties of six lactobacilli with probiotic features in an in vitro model of macrophage-like cells and to test these pooled probiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…studied the immunomodulatory effects of six lactobacilli containing probiotic properties in an in vitro model of macrophage cells and their anti-tumor properties in a rat model of CRC. They indicated that the bacteria could induce the release of pro- and anti-inflammatory cytokines, including IL-1β, TNF-α, IL-18, and IL-23, in co-culture of lactobacilli with M1- and M2-like macrophages, whereas the bacteria oral administration led to a decrease in tumor multiplicity, numbers, and volume, as well as restore of colon length and increase in the production of IL-18 [ 99 ]. In another study, a clinical trial found that oral administration of probiotic Saccharomyces boulardii could downregulate the levels of both pro- and anti-inflammatory cytokines, including IL-10, IL-23A, and IL-1β, while the incidence of infectious complications in patients receiving probiotic was 13.3% compared to 38.8% in the control group [ 100 ].…”
Section: Strategies Of Gut Microbiota Modulationmentioning
confidence: 99%
“…studied the immunomodulatory effects of six lactobacilli containing probiotic properties in an in vitro model of macrophage cells and their anti-tumor properties in a rat model of CRC. They indicated that the bacteria could induce the release of pro- and anti-inflammatory cytokines, including IL-1β, TNF-α, IL-18, and IL-23, in co-culture of lactobacilli with M1- and M2-like macrophages, whereas the bacteria oral administration led to a decrease in tumor multiplicity, numbers, and volume, as well as restore of colon length and increase in the production of IL-18 [ 99 ]. In another study, a clinical trial found that oral administration of probiotic Saccharomyces boulardii could downregulate the levels of both pro- and anti-inflammatory cytokines, including IL-10, IL-23A, and IL-1β, while the incidence of infectious complications in patients receiving probiotic was 13.3% compared to 38.8% in the control group [ 100 ].…”
Section: Strategies Of Gut Microbiota Modulationmentioning
confidence: 99%
“…Similarly, the probiotic strains Lactobacillus plantarum and Lactobacillus. salivarius were able to augment IL-18 production in both in vitro and rat models of CRC [ 104 ]. In addition to LAB species, yeast is also able to immunomodulate IL-18 levels.…”
Section: Probiotics In Crcmentioning
confidence: 99%
“…Lactic acid bacteria (briefly identified as LABs) are beneficial microorganisms (also known as probiotics) that help improve the nutrition of foods, balance the microbial population of the gut microbiota, strengthen the immune and intestinal tract, and lower cholesterol ranges in the blood [91]. Although these bacteria are present in many foods, most experiments have been performed to study them in the laboratory and on dairy products [92].…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%